PENGARUH ATTRACTION, AMENITIES, ACCESSIBILITY, DAN ANCILLARY TERHADAP KEPUASAN DAN LOYALITAS WISATAWAN NUSANTARA KE PANTAI PANDAWA, BADUNG - Kusuma, Theodorus Wijaya; Dewi, LGLK.; Agus Wikanatha Sagita, Putu (Department of Tour and Travel Studies, Faculty of Tourism, Udayana University, 2023)
Attraction, amenities, accessibility, and ancillary are 4 important components in a tourist attraction, if these components are managed and developed optimally, it will increase the satisfaction and loyalty of tourists visiting a tourist attraction. One of the tourist attractions that has attraction, amenities, accessibility, and ancillary components is the Pandawa Beach tourist attraction. This study aims to determine the effect of attraction, amenities, accessibility, and ancillary on the satisfaction and loyalty of domestic tourists visiting Pandawa Beach, Badung Regency, Bali. The data sources of this research are primary data and secondary data, while the types of data in this study are qualitative data and quantitative data. The data collection techniques used in this research are observation, questionnaires, interviews, documentation, and literature review. The sampling technique and informants in this study used accidental sampling technique with a sample size of 100 respondents. The data analysis technique used in this research is descriptive statistical analysis with the help of SmartPLS software. The results of this study indicate that attraction, amenities, accessibility, and ancillary have a direct positive and significant effect on domestic tourist satisfaction and domestic tourist loyalty and domestic tourist satisfaction has a positive and significant effect on domestic tourist loyalty. Then, attraction, amenities, accessibility, and ancillary have an indirect positive and significant effect on the loyalty of domestic tourists through the satisfaction of domestic tourists as mediation.